Nonadiabatic heating in magnetic reconnection. Issue 7 (22nd July 2014) - Ma, Xuanye; Otto, Antonius
Abstract Plasma transport process as a fundamental problem in magnetospheric physics is often associated with strong nonadiabatic heating. At the magnetopause, observations show an increase of specific entropy (i.e., S = p/ργ) by 2 orders of magnitude from the magnetosheath into the magnetosphere. In the near‐Earth magnetotail, particle injection requires strongly entropy depleted plasma bubbles, and their evolution can be strongly modified in the presence of nonadiabatic heating. In this study, one of the critical plasma transport mechanisms, magnetic reconnection, is investigated as a nonadiabatic process in the framework of MHD. It is important to examine whether magnetic reconnection can provide sufficient nonadiabatic heating to explain the observed plasma properties and to identify plasma conditions that allow such strong nonadiabatic heating. We demonstrate that the entropy can indeed strongly increase associated with magnetic reconnection provided that the plasma beta (i.e., the ratio of thermal to magnetic energy density) is low in the inflow region of reconnection.